Peer Counseling Based on Mindful Learning to Reduce Students’ Academic Anxiety in Border Areas: A Community Service Approach (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to reduce students’ academic anxiety through peer counseling based on mindful learning at Madrasah Aliyah Al Ikhlas Nunukan, North Kalimantan. A participatory approach was employed, including socialization, training, implementation, mentoring, and evaluation stages. Selected students were trained as peer counselors using basic counseling skills integrated with mindful learning techniques such as mindful breathing, focused attention, and acceptance strategies. The results indicated a significant improvement in students’ understanding of academic anxiety and their ability to manage stress, as evidenced by pre- and post-test comparisons. Additionally, a Peer Counselor Mindful Learning community was successfully established as a sustainable support system. These findings suggest that integrating peer counseling with mindful learning is an effective and contextually relevant strategy for enhancing students’ psychological well-being in resource-limited areas.